Infecção viral em Apis mellifera : detecção molecular, expressão de AmToll-1 e proteoma diferencial - Almeida, Luciana de Oliveira (2011)
CHAPTER II: In Brazil the Tocantins' State has three biomes, savannah, Amazon forest and caatinga, beyond transitional regions between them. These biomes harbor a diversity of species including several pollinators as bees. With the phenomenon of Colony Collapse Disorder (CCD), researchers worldwide are seeking an answer to the high mortality of bees and they claim that viruses could be as one of them. We are looking for seven viruses in the State by RT-PCR. Our analysis confirmed the presence of two viruses ABPV and DWV, showing that the northern region is already contaminated and prophylactic measures should be taken by beekeepers to avoid significant losses as occurred in the United States and Europe. CHAPTER III: Insects are a group extremely successful over time, due including their highly developed innate immune system and have colonized all the terrestrial habitats. In this study, we characterized and quantified transcripts by real-time PCR of the AmToll-1 gene in bees infected with deformed wing virus (DWV) and co-infected with acute bee paralysis virus (ABPV) and DWV. The analysis "in silico" showed that this gene has domain leucine-rich typical of Toll receptor. The quantification of transcripts of Toll gene revealed increased their expression significantly in individuals with co-infection. These data show that viral co-infection can modulate levels of gene transcripts AmToll-1. CHAPTER IV: Several tools are used to identify and quantify the different pathogens that attack the bees. We evaluated gene expression in infected bees with deformed wing virus (DWV) and bees co-infected with acute bee paralysis virus (ABPV) by analyzing two-dimensional gel SDS-PAGE. The preliminary results showed that there was a change in protein profile when compared to uninfected bees, with an increase of transcripts between bee infected and co-infected by the virus.